Effect of the documentary credit opening procedures on The obligate of time limits prescribed by the contract - ابراهيم نوال طارق; علوان غسان مصعب (Journal of Economics and Administrative Sciences, 2017)
This research aims to analyze the effect between letter of credit opening and implementation procedures which considered one of the most important Foreign services submitted by bank institutions to their customers on Time contracted time limit commitment contract by some Iraqi commercial banks, descriptive analytical method used in This research The questionnaires designed a tool main research to gather information to get to know the effect , Seventy questionnaire forms were distributed, sixty seven forms were analyzable , The answers were analyzed by the arithmetic mean and standard deviation and test the level of influence between variables simple linear regression. The result showed the presence of effect and According to the conclusion, many recommendations were formed the most prominent was expansion in the financing of opening letters of credit operations for the benefit of the Iraqi buyers, The administration to identify enough time to prepare a letter of credit requirements , and settling of opened accounts then repack to the government safe.